Screening of serum 25-hydroxyvitamin D levels among elderly Egyptians admitted to the orthogeriatric unit by fracture hip - Ahmed Rabiee; Mohamed AboElsoud; Sayed M. Seif El Nasr; Sameh Abouzeid (SpringerOpen, 2020)
Abstract Background Vitamin D deficiency increases muscle weakness and pain leading to reduced power and function, increased bone turnover and increased risk of falls and hip fractures in elderly. We postulated that vitamin D deficiency in sunny Egypt should be lower than western countries so we screen for prevalence of vitamin D deficiency among all elderly patient admitted to orthogeriatric unit by fracture hip. Results Our study showed that vitamin D deficiency is common in elderly Egyptian patients admitted to orthogeriatric unit with hip fractures. Of the study group (n 290 patients) vitamin D levels were sufficient (30 ng/dl or more) in 24 patients (8.3%) and insufficient (between 20 ng and 30 ng) in 125 patients (43.1%) and deficient (less than 20) in 141 patients (48.7%). Among the study group, female patients had lower levels of vitamin D (18.8 ± 6.9) compared to males (20.5 ± 6.7) P value 0.034. Although our study failed to link different levels of vitamin D with activity of daily life: P value was (0.116) in bathing, (0.058) in dressing, (0.115) in toileting and (054) in transfer. A little difference was found in feeding (0.036) and previous fall (0.011) and cognitive impairment; MiniCOG < 3 P value 0.017. Both previous falls and cognitive decline are in turn linked to increased fracture risk Conclusion Hypovitaminosis D is common among older patients with hip fractures even in sunny Egypt remaining slightly lower than its prevalence in western countries. Although no direct significant correlations with activity of daily life, vitamin D deficiency was associated with higher risks of previous falls and cognitive impairment both in turn increases the risk of fractures.